Pelaksanaan Perjanjian Babalu Dalam Masyarakat Negeri Sanahu - Yoseph Batlolona; Barzah Latupono; Sarah Selfina Kuahaty (Faculty of Law, Universitas Pattimura, 2023)
Introduction: In everyday life, humans cannot be separated from carrying out agreement activities, both written and unwritten.Purposes of the Research: To study and analyze the implementation of the babalu agreement in Negeri Sanahu, To review and design a babalu agreement that can provide benefits to the parties, As one of the requirements to complete studies at the Faculty of Law, University of Pattimura.Methods of the Research: Normative juridical research method, which is to obtain data from the library in the form of documents, books, magazines and other literature related to writing. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through qualitative analysis, namely the data obtained and then arranged systematically for further qualitative analysis based on scientific disciplines. civil law to achieve clarity of issues to be discussed.Results of the Research: Babalu agreement is an agreement that is often used by people in the State of Sanahu, West Seram Regency with certain provisions and there are rights and obligations between land owners and sharecroppers. If the agreement made and agreed upon by the parties and witnesses (customary leaders) is violated, the violator will receive sanctions in the form of termination of work if the violation is on the part of the sharecropper, and if the land owner violates the law, the results that are managed completely belong to the sharecropper. Without repaying the land owner. If the agreement is violated by one of the parties, then the legal consequences are in accordance with Article 1338 of the Civil Code, namely if anyone who violates the agreement will receive a penalty as stipulated in the law.